On the increase of chromosome mutations under random mating. - Bengtsson, B; Bodmer, W (1976)
After a short introduction on karyotypes and chromosome mutations, we review the ways by which a chromosome mutation can increase in a random mating population, despite the mutation's deleterious effect on the fertility of heterozygotes. Random drift, segregation distortion, viability advantage, and recombination modification are the mechanisms considered. When possible, the models are illustrated with examples of chromosome mutations involving autosomes in mammals, but the arguments apply, of course, to any genetic factor in any outbreeding species that causes a fertility decrease in heterozygotes. © 1976.